BECOMING A CARING LEADER: STRATEGIES FOR IMPROVING INMATE DEVELOPMENT - Sulthon, Hilal Khabib As; Priyatmono, Budi (Universitas Nusa Cendana, 2025)
Prisoner development is the core of the correctional system, which aims to prepare inmates to return to society as productive individuals. One of the determining factors for the success of the development program is the leadership implemented by correctional officials, especially the head of the correctional institution (prison) and community counselors (PK). This article discusses the concept of caring leadership and its strategic role in improving the quality of prisoner development. Through a descriptive qualitative approach and literature study, this article finds that leaders who demonstrate empathy, openness, effective communication, and consistency in action are able to create a more humane coaching environment, support rehabilitation, and reduce recidivism. Keywords: Caring Leadership; Correctional; Prisoner Development; Rehabilitation; Recidivism